2021
DOI: 10.1002/14651858.cd013870.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy for atopic eczema

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 151 publications
1
9
0
1
Order By: Relevance
“…Our previous studies [3][4][5] found that the most common first line, topical non-medicated therapy for adults and children with moderate to severe AD was phototherapy. In these surveys, NBUVB was the most frequently prescribed, then followed by PUVA and finally UVA1 was the least frequently prescribed (mainly due to lack of access).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies [3][4][5] found that the most common first line, topical non-medicated therapy for adults and children with moderate to severe AD was phototherapy. In these surveys, NBUVB was the most frequently prescribed, then followed by PUVA and finally UVA1 was the least frequently prescribed (mainly due to lack of access).…”
Section: Discussionmentioning
confidence: 99%
“…European (EU) guidelines exist to guide us in our use of phototherapies for AD 1,2 . In our previous survey of AD therapies 3–5 phototherapy was found to be the most frequently initiated therapy after topical treatment for moderate‐to‐severe AD among European dermatologists, in particular NBUVB. However, evidence for its efficacy, impact on quality of life, cost‐effectiveness and short‐ and long‐term safety is weak with respect to real‐life usage, as evidenced by a recent Cochrane review 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Kolejnym rzutem w leczeniu jest fototerapia. Wykorzystywane jest światło UVA, UVB oraz psolareny w połączeniu z UVA (PUVA) [21]. Nowymi lekami dopuszczonymi w leczeniu atopowego zapalenia skóry są upadacytynib (inhibitor JAK), dupilumab (przeciwciało monoklonalne przeciwko IL-4, IL-13) oraz crisaborole (inhibitor DPE-4).…”
Section: Leczenieunclassified
“…Traditionally, treatment of AD has consisted of systemic drugs (cyclosporine, methotrexate, azathioprine, and mycophenolate mofetil), topical ointments (corticosteroids, calcineurin inhibitors) and phototherapies (NB-UVB, UVA1, PUVA) 15 , 16 . More recently, administrations of more specific biological agents, e.g.…”
Section: Introductionmentioning
confidence: 99%